Pesnik in homilet Anton Šerf kot nosilec poznih razsvetljenskih tokov v vzhodnoštajerskem knjižnojezikovnem prostoru - Vičar, Branka (Jezik in slovstvo, 2003)
The paper characterises the poet and homiletic expert, Anton Šerf, as one of the leading representative of late Enlightenment currents in the language and literature of Eastern Styria in the first half of the 19th century. It presents the spiritual incentives for and literary examples of his work and the responses to him in Slovene literary history. It discusses Šerf's sermons and secular poetry and analyses the poetic form.
Keywords: Šerf, Anton; Slovene literature; slovenska književnost; poezija; 19.st.; Age of Enlightenment; razsvetljenstvo; history of literature; literarna zgodovina